Para além das fronteiras e dos limites: adolescentes migrantes marroquinos entre desejo, vulnerabilidade e risco - Vacchiano, Francesco (2014)
This contribution analyzes and discusses the case of the migration of “unaccompanied” children and adolescents between Morocco and Europe. This analysis was originally presented as a contribution to the Project “Anthropology of Interfaces” (FCT/CAPES). The article examines the ways in which young migrants give meaning to the world and to the experience of mobility, in an attempt to explore the construction of the youth’s experience between contemporary global and (g)local worlds of experience and meaning. The theoretical perspective inspiring the study lies at the intersection of anthropology, psychology and migration studies and is based on the concept of subjectivity, understood as a form of orientation to the world and embodiment of historically and politically defined norms, values and meaning. This orientation influences the imagination and defines specific forms of thinking, acting, speaking, suffering and giving meaning to existence. The article shows that the subjective construction of postcolonial youth and their families is moulded upon a globally-fashioned “desire for modernity and participation”, which clashes with the normative process imposed by the new “discipline of the borders” in Europe, manifested through the bureaucratic and administrative procedures of the so-called “reception”. The combination of these two dynamics concurs in producing the experience of marginality and the following risk also in terms of “disposition to be sanctioned”. Conclusions delve into the paradox of a process in which young migrants are pushed back to the prescribed marginal place in the world which the infringement of the border had tried to subvert.